Campaign Strategy for Village Head Candidates in the Village Head Election in Arallae Village, Kahu District, Bone Regency - Sri Rahayu Juniati; Septi Hikmatun; Nirwana, Nirwana; Indra Anugrah; Muhlis Hajar Adiputra (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This study aims to determine how the campaign strategy of village head candidates in the implementation of village head elections in Arallae Village, Kahu Subdistrict, Bone Regency. This research is a qualitative study intended to provide a clear overall picture and description of the existing problems. Data were collected through observation, in-depth interviews and documentation. The data obtained was analysed based on predetermined indicators by looking at the results of observations, interviews, and documentation from research informants, which were then described in the form of words and sentences, which then became a researcher's conclusion. This research was conducted with informants from the Head of Arallae Village, Kahu Subdistrict, Bone Regency, Village Head Election Committee, Election Supervisor, Elected Village Head Winning Team and Community Leaders of Arallae Village, Kahu Subdistrict, Bone Regency. The results showed that the campaign strategy of the village head candidates in the village head election in Arallae Village, Kahu Subdistrict, Bone Regency used the most effective house-to-house campaign technique because it could communicate and interact directly with the community as seen from the results of the votes obtained compared to the direct mass and indirect mass campaign techniques which were less effective, but could be a driving factor in community participation.